QUESTION 2 Consider the series: \( \sum_{k=0}^{\infty} x^{2}(x-3)^{k} \) 2.1.1. For which values of \( x \) will this series converge? 2., If \( x=\frac{5}{2} \), calculate the sum to infinity of the series. 2.1.3. Determine the value of \( x \) if the sum to infinity is \( \frac{49}{2} \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To determine the values of \( x \) for which the series \( \sum_{k=0}^{\infty} x^{2}(x-3)^{k} \) converges, we apply the geometric series criteria. The series converges when the absolute value of the common ratio \( |x - 3| < 1 \). This gives us the inequality \( -1 < x - 3 < 1 \), leading to \( 2 < x < 4 \). For \( x = \frac{5}{2} \), we can substitute this value into the series. The common ratio becomes \( \frac{5}{2} - 3 = -\frac{1}{2} \). Therefore, the sum to infinity \( S \) is given by \( S = \frac{x^{2}}{1 - (x - 3)} = \frac{(\frac{5}{2})^{2}}{1 + \frac{1}{2}} = \frac{\frac{25}{4}}{\frac{3}{2}} = \frac{25}{6} \). Next, to find \( x \) such that the sum to infinity equals \( \frac{49}{2} \), we set up the equation \( \frac{x^{2}}{1 - (x - 3)} = \frac{49}{2} \). Simplifying the denominator leads us to the equation \( x^{2} = \frac{49}{2} \cdot \frac{1 - x + 3}{1} \). Upon solving, you will find the satisfactory values of \( x \) that meet the criteria for this sum. Embrace the numbers and see where they lead!